Associations of Menstrual Cycle Regularity and Length With Cardiovascular Diseases: A Prospective Study From UK Biobank - Chensihan Huang; Bingquan Lin; Youwen Yuan; Kangli Li; Bingyan Xu; Peizhen Zhang; Xueyun Wei; Weiwei Wang; Wenhui Liu; Yajuan Deng; Deying Liu; Jiayang Lin; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background The association between menstrual cycle characteristics and cardiovascular outcomes remains unclear. This study was undertaken to evaluate whether menstrual cycle regularity and length throughout the life course are associated with cardiovascular outcomes. Methods and Results This cohort study included 58 056 women who had no cardiovascular disease (CVD) at baseline and reported their menstrual cycle regularity and length. Hazard ratios (HRs) and 95% CIs for CVD events were estimated using Cox proportional hazards models. During the median 11.8 years of follow‐up, 1623 incident CVD cases were documented, including 827 incident cases of coronary heart disease, 199 myocardial infarctions, 271 strokes, 174 cases of heart failure, and 393 cases of atrial fibrillations. Compared with women with regular menstrual cycles, the HRs for women with irregular menstrual cycles were 1.19 (95% CI, 1.07–1.31) for CVD events and 1.40 (95% CI, 1.14–1.72) for atrial fibrillation. The multivariable‐adjusted HRs for short (≤21 days) or long (35 days) menstrual cycles during follow‐up were 1.29 (95% CI, 1.11–1.50) and 1.11 (95% CI, 0.98–1.56) for CVD events, respectively. Similarly, long or short cycle length were more likely to be associated with increased risk of atrial fibrillation (HR, 1.30 [95% CI, 1.01–1.66]; and HR, 1.38 [95% CI, 1.02–1.87]), and short cycle length was more likely to be associated with increased risk of coronary heart disease and myocardial infarction. However, these associations for stroke and heart failure were not significant. Conclusions Long or short menstrual cycle length was associated with increased risks of CVD and atrial fibrillation but not myocardial infarction, heart failure, or stroke. Short cycle length was associated with a greater risk of coronary heart disease and myocardial infarction.